Biochemical and biophysical characterization of a mycoredoxin protein glutaredoxin A1 from Corynebacterium pseudotuberculosis - Eberle, Raphael J. [UNESP]; Kawai, Liege A. [UNESP]; de Moraes, Fabio R. [UNESP]; Tasic, Ljubica; Arni, Raghuvir K. [UNESP]; Coronado, Monika A. [UNESP] (Elsevier, 2018)
Glutaredoxin A1 from Corynebacterium pseudotuberculosis was shown to be a mycoredoxin protein. In this study, we established a process to overexpress and purify glutaredoxin A1. The aim of this study was the investigation of the Glutaredoxin A1 from C. pseudotuberculosis behavior under different redox environments and the identification of lead molecules, which can be used for specific inhibitor development for this protein family. A quantitative assay was performed measuring the rate of insulin reduction spectrophotometrically at 640 nm through turbidity formation from the precipitation of the free insulin. Glutaredoxin A1, at 5 μM concentration, accelerated the reduction process of 0.2 mM insulin and 1 mM DTT. The pH optimum of the reaction was 7.4. In the presence of DTT and ESH the glutaredoxin A1 presents similar activity, and its activity is reduced by 50% in the presence of GSH. Additional function for ESH in the redox metabolism of C. pseudotuberculosis is suggested. A combined STD and Chemical Shift – NMR approach was employed to study the effects of potential inhibitors on the structure of glutaredoxin A1 from Corynebacterium pseudotuberculosis. The inhibitory potential of four ligands (heparin, suramin, hesperetin – Hst, and hesperidin - Hsp) against glutaredoxin A1 is discussed.
Keywords: CD spectroscopy; Corynebacterium pseudotuberculosis; Glutaredoxin; Inhibitors; NMR